BASIC PRINCIPLES AND POSSIBILITIES OF TRANSLATION OF PROVERBS FROM ENGLISH INTO UZBEK LANGUAGE: BASIC PRINCIPLES AND POSSIBILITIES OF TRANSLATION OF PROVERBS FROM ENGLISH INTO UZBEK LANGUAGE - Tnibaeva, Gulmira (Журнал иностранных языков и лингвистики, 2025)
The issue of bilingualism and trilingualism is of great importance not only in language learning, but also in the formation of a person and his worldview. Translation is one of the main factors in language learning. Translation serves the interests of friendship and cooperation between nations. Translation accelerates the development of languages, increases and improves vocabulary.